Analyzing the Impact of Brand Equity towards Purchase Intention in Automotive Industry: A Case Study of ABC in Surabaya - Cynthia Ratna Santoso; Tabita Ella Cahyadi (iBuss Management, 2014)
The rapid growth in Indonesia’s automotive industry makes it becomes a lucrative market for automaker companies. Of all Japanese car brands in Indonesia, ABC and XYZ are considered the biggest rivals. Hence, strong brand equity should be built, not only for distinguishing themselves from competitors, but also for stimulating consumers’ purchase intention. Consequently, this research aims to analyze the impact of brand equity towards purchase intention in automobile industry. This research uses Aaker’s brand equity theory, covering brand awareness, brand association, perceived quality, and brand loyalty.In this research, the writers use simple random sampling in which the population is Surabaya people who own or used to own both ABC and XYZ cars. 125 samples collected from the research are analyzed using Multiple Linear Regression Analysis and comparative analysis. The result shows that brand equity simultaneously has a significant influence towards purchase intention while only brand association and brand loyalty individually have a significant influence towards purchase intention. According to comparative analysis, ABC has a better brand association than XYZ, but it has lower brand loyalty than XYZ. Keywords: brand equity, purchase intention, automobile, Surabaya